Age-period-cohort analysis of early syphilis in Shandong province from 2006 to 2020 - Zhenghao WU; Yu DONG; Xinyu CAI; Fengyue ZHANG; Hongqing LIU (Zhongguo gonggong weisheng)
ObjectiveTo investigate the incidence and trends of early syphilis in Shandong province and provide references for syphilis prevention and control. MethodsData for this study were obtained from the China Public Health Science Data Center. Joinpoint regression was used to analyze trends in incidence rates, and age-period-cohort (APC) models were used to analyze the effects of age, period, and birth cohort. ResultsFrom 2006 to 2020, the incidence of early syphilis in Shandong province initially increased and then decreased. The average annual percentage change (AAPC) for primary and secondary syphilis was 6.02% and 6.25%, respectively. The proportion of cases in the 0–19 and ≥60 age groups has been increasing. Age-period-cohort analysis showed that the 20–24 age group had the highest incidence of early syphilis, with incidence rates of 10.47/100 000 and 16.67/100 000 for primary and secondary syphilis, respectively. The risk of disease first increased and then decreased over time. With the progression of birth cohorts, the risk of disease continued to increase, peaking in 2006–2010, with relative risks (RR) of 6.38 and 8.58 for primary and secondary syphilis, respectively. ConclusionsThe incidence of early syphilis in Shandong province showed a trend of first increasing and then decreasing. The 20–24 age group had the highest risk of disease, and the proportion of cases in the 0–19 and ≥60 age groups has been increasing.